Inclusive Growth Revisited : Measurement and Determinants - Anand, Rahul; Mishra, Saurabh; Peiris, Shanaka J. (World Bank, Washington, DC, 2015)
The call for inclusive growth has been unanimously broadcasted by policy makers across the world. The Arab spring, the growing divide between Main Street and Wall Street in advanced economies, and the three-speed world economy have placed inclusive growth at the forefront of policy debates. However, efforts to measure and assess the determinants of inclusive growth have remained limited. What is inclusive growth? How can the micro and macro dimensions of inequality and growth be integrated to reflect both the pace and distribution of economic growth? What has driven inclusive growth in emerging markets?